Loyalty in Cooperatives Through the Service Dominant Logic View - Klafke, Renata; Moreira Pinto, Guilherme; Tânia Picinin, Cláudia (Cooperativismo & Desarrollo, 2022)
This paper offers a theoretical analysis of agricultural cooperatives´ assistance to its members to innovate as a value proposition of loyalty. The Service Dominant Logic (SDL) is used as the theoretical background. Through a logical reasoning we infer that value generation through a fundamental service provision like innovation sharing could strengthen cooperator’s loyalty. This is for its relational perceived value, where actions and interactions occur to cocreate. This paper provides correlations from the theory and practice which help the reader to get a better picture of the idea exposed here. The understanding about whose actors cocreate value and what values propositions are important for associates and cooperative as an institution to survive allow cooperatives to orient efforts towards its service offer as a way of enhancing loyalty and strengthening improvement and commitment.
Keywords: services; service dominant logic; cooperatives; innovation sharing